The integration of national minorities in the Samtskhe-Javakheti and Kvemo Kartli provinces of Georgia - Wheatley, Jonathan (2009)
Abstract: 'This paper aims to explore the extent to which national minorities in the Georgian provinces of Kvemo Kartli and Samtskhe-Javakheti are integrated into the economic and political life of Georgia and to investigate how government policy in the aftermath of the Rose Revolution of November 2003 has affected the relationship between the state and minority communities in these two regions. It is divided into eight parts. First I provide a general overview of the main characteristics of the population of the two provinces in terms of ethnicity and language use. The second part turns to the economy of the two regions, focusing on both agricultural and industrial production. The next section turns to state-society relations by showing how government policy in the fields of education, local government, infrastructure and economic development has impacted upon the integration of national minorities in the two provinces. The fourth section explores in greater depth the modes of local governa